Hard carbon negative electrode material and preparation method thereof, mixed negative electrode material, and secondary battery

Through passivation and carbon coverage of hard charcoal front drives, the problem of low efficiency and poor circulation performance of hard charcoal negative materials for hard charcoal negative materials has been solved. Essence

CN115893369BActive Publication Date: 2025-01-28GANZHOU LITAN NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211487336.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-01-28
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The first-time efficiency of hard carbon negative electrode material is low, resulting in poor effect in actual applications, and the volume expansion is large during charging and discharging, affecting the cycling performance.

Method used

By passivating the hard charcoal front drive, the passivation layer is formed to reduce the activity of lithium or sodium, and carbon coverage treatment after passivation treatment is performed to improve the stability and safety of the material.

Benefits of technology

It significantly improves the first efficiency and circulation performance of hard charcoal negative materials, improves its power and circulation performance in the secondary battery, while improving the initial charging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115893369B_ABST
    Figure CN115893369B_ABST
Patent Text Reader

Abstract

The present invention provides a hard carbon negative electrode material and a preparation method thereof, a mixed negative electrode material, and a secondary battery, and relates to the technical field of hard carbon negative electrode materials, including: a hard carbon precursor is subjected to passivation treatment to obtain a hard carbon negative electrode material; wherein the hard carbon precursor includes at least one of a pre-lithiation hard carbon precursor and a pre-sodium hard carbon precursor; the passivation treatment includes: under a protective atmosphere, the sodium and / or lithium in the hard carbon precursor reacts with a passivating substance to form a passivation layer to reduce the activity of the sodium and / or lithium. The present invention can improve the stability and safety of the pre-lithiation or pre-sodium precursor in the air, can improve the processing performance of the pre-lithiation or pre-sodium hard carbon negative electrode material when used as a secondary battery negative electrode material, especially can improve the slurry stability of the negative electrode sheet during the preparation process, and can greatly improve the first efficiency of the material, and at the same time is conducive to the hard carbon negative electrode material having good cycle performance in the battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hard carbon negative electrode materials, and in particular to a hard carbon negative electrode material and a preparation method thereof, a mixed negative electrode material, and a secondary battery. Background Art

[0002] Negative electrode materials can be divided into two categories: carbon materials and non-carbon materials. Carbon materials include graphite, hard carbon, soft carbon, and mesophase carbon microspheres, while non-carbon materials include silicon-based materials, lithium titanate, and tin-based materials.

[0003] At present, the most widely used and largest-selling negative electrode material in the market is graphite. However, the theoretical specific capacity of graphite negative electrode is relatively low (only 372mAh / g), and its high-rate continuous charge and discharge capability and low-temperature performance are difficult to be effectively improved.

[0004] Hard carbon refers to carbon materials that are difficult to graphitize. They are formed by the thermal decomposition of high molecular polymers. Hard carbon materials have an interlaced layered structure with large spacing between carbon layers. Lithium ions can be embedded and extracted from different angles, thereby increasing the diffusion rate of lithium ions and achieving rapid charging and discharging of the material. At the same time, the presence of a large number of micropores gives hard carbon materials more lithium embedding space. Its reversible specific capacity is generally 300-700mAh / g, and can even exceed 1000mAh / g, which is much larger than the theoretical capacity of graphite 372mAh / g. The structure of hard carbon materials is stable and the volume expansion during charging and discharging is very small. It has excellent long-cycle performance, its lithium embedding potential can be higher than 0.2V, and its safety performance is good. The above excellent performance of hard carbon materials matches the long-cycle performance requirements of future pure power batteries / energy storage batteries, and the high energy density and high power requirements of 48V start-stop batteries / PHEV power batteries / consumer batteries / supercapacitors.

[0005] However, the structural advantages of hard carbon materials also bring corresponding disadvantages. During the preparation process, a large number of lattice defects will be generated in the internal structure, which leads to the fact that during the lithium insertion process, lithium ions are not only embedded in the carbon atom layers, but also in these lattice defects. Although the specific capacity of the hard carbon negative electrode can be significantly improved, these lattice defects also lead to the low first coulomb efficiency of the hard carbon negative electrode material. At present, most of the hard carbon materials that can be commercially produced on the market are low-performance ordinary hard carbons with low reversible specific capacity (≤400mAh / g) and poor first efficiency (≤85%). The actual application of negative electrode materials is not good, which leads to low market penetration.

[0006] In application areas where the performance of traditional graphite negative electrodes is difficult to meet, mixing more than 10% of hard carbon materials can greatly improve the power density, low temperature performance and long cycle performance of the battery, but it will reduce the initial efficiency of the graphite negative electrode material, resulting in low positive electrode capacity and reducing the energy density of the battery. At this stage, the biggest drawback of hard carbon negative electrode materials is the low initial efficiency, which is generally 70-85%, while the initial efficiency of graphite negative electrodes can reach more than 94%. Therefore, if the initial efficiency of hard carbon negative electrode materials can be greatly improved, as long as it reaches more than 90%, hard carbon negative electrodes may replace graphite negative electrodes on a large scale and become the next generation of mainstream negative electrode materials.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] One of the purposes of the present invention is to provide a method for preparing a hard carbon negative electrode material, which can improve the stability and safety of the precursor after pre-lithium or pre-sodium in the air, improve the processing performance, and enhance the initial efficiency of the material and the cycle performance in the battery system.

[0009] The second object of the present invention is to provide a hard carbon negative electrode material having the characteristics of high specific capacity and high initial efficiency, as well as good processing performance and excellent cycle performance.

[0010] The third object of the present invention is to provide a mixed negative electrode material having the characteristics of high specific capacity, high initial efficiency, good processing performance and excellent cycle performance.

[0011] A fourth object of the present invention is to provide a secondary battery having high power performance and cycle performance as well as better initial charge and discharge efficiency.

[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0013] In a first aspect, a method for preparing a hard carbon negative electrode material comprises the following steps:

[0014] The hard carbon precursor is passivated to obtain the hard carbon negative electrode material;

[0015] The hard carbon precursor includes a modified hard carbon precursor;

[0016] The modified hard carbon precursor includes at least one of a pre-lithiation hard carbon precursor and a pre-sodium hard carbon precursor;

[0017] The passivation process comprises the following steps:

[0018] Under the protective atmosphere, the sodium and / or lithium in the hard carbon precursor reacts with the passivation substance to form a passivation layer, thereby reducing the activity of the sodium and / or lithium in the hard carbon precursor.

[0019] Further, the protective atmosphere includes at least one of nitrogen and argon;

[0020] Preferably, the passivating substance includes at least one of water, alcohol, acid, base and oxide;

[0021] Preferably, the alcohol includes at least one of methanol, ethanol, n-propanol, isopropanol, butanol and ethylene glycol;

[0022] Preferably, the acid comprises at least one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, citric acid, formic acid, benzoic acid, acrylic acid, acetic acid, propionic acid, stearic acid, hypochlorous acid and boric acid;

[0023] Preferably, the base comprises at least one of lithium carbonate, sodium carbonate, lithium hydroxide and sodium hydroxide;

[0024] Preferably, the oxide includes at least one of manganese heptoxide, sulfur trioxide, phosphorus pentoxide, chromium trioxide, sodium oxide, lithium oxide, calcium oxide, barium oxide, manganese oxide and magnesium oxide.

[0025] Furthermore, the carbon layer spacing d of the hard carbon precursor is 002 0.35 to 0.43 nm, preferably 0.36 to 0.42 nm;

[0026] Preferably, the lithium content in the pre-lithiated hard carbon precursor is 0.5 to 10 wt%;

[0027] Preferably, the sodium content in the pre-sodiumized hard carbon precursor is 0.5-10 wt %.

[0028] Furthermore, the method for preparing the modified hard carbon precursor comprises the following steps:

[0029] The hard carbon raw material is first sintered in an inert atmosphere to obtain a precursor, and then mixed with a lithium source and / or a sodium source for a second sintering so that the precursor contains lithium and / or sodium, thereby obtaining a modified hard carbon precursor;

[0030] Preferably, the inert atmosphere comprises nitrogen;

[0031] Preferably, the temperature of the first sintering is below 1800°C, preferably 1000-1600°C;

[0032] Preferably, the lithium source includes at least one of lithium powder, lithium tetrafluoroborate, lithium hydride, lithium acetate, lithium stearate, lithium hexafluorophosphate, lithium nitride, lithium fluoride, lithium chloride and lithium bromide;

[0033] Preferably, the sodium source includes at least one of sodium powder, sodium sulfide, sodium oxide, sodium peroxide, sodium hypochlorite, sodium hydride, sodium nitride, sodium thiosulfate, sodium ethoxide, sodium dichloroacetate, sodium ascorbate and disodium maleate;

[0034] Preferably, the second sintering temperature is 300-900°C.

[0035] Furthermore, after the passivation treatment, the step of carbon coating the hard carbon precursor to form a carbon coating layer on the surface of the hard carbon precursor is also included;

[0036] Preferably, the average thickness of the carbon coating layer is 10 to 2000 nm;

[0037] Preferably, the carbon coating layer comprises a coating layer formed after thermal decomposition of a thermal decomposition raw material;

[0038] Preferably, the thermal decomposition raw material includes at least one of asphalt, methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane, hexane, polyvinyl chloride resin, polyamide resin, polyamide, polyethylene glycol, polyethylene, polyvinyl chloride, polystyrene and polypropylene.

[0039] In a second aspect, a hard carbon negative electrode material is prepared by any of the preparation methods described above.

[0040] Furthermore, the specific surface area of ​​the hard carbon negative electrode material is 1 to 6 m 2 / g;

[0041] Preferably, the median particle size D50 of the hard carbon negative electrode material is 3 to 15 μm;

[0042] Preferably, the water content of the hard carbon negative electrode material is below 1wt%;

[0043] Preferably, the tap density of the hard carbon negative electrode material is 0.6 to 1.0 g / cm 3 ;

[0044] Preferably, the compaction density of the hard carbon negative electrode material at a pressure of 5T is 0.8 to 1.3 g / cm 3 .

[0045] In a third aspect, a mixed negative electrode material comprises the hard carbon negative electrode material described in any one of the above items and other negative electrode materials;

[0046] Preferably, the mass proportion of the hard carbon negative electrode material is more than 10%;

[0047] Preferably, the other negative electrode materials include at least one of other carbon-based negative electrode materials and silicon-based negative electrode materials;

[0048] Preferably, the other carbon-based negative electrode materials include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, carbon nanotubes and graphene;

[0049] Preferably, the silicon-based negative electrode material includes at least one of elemental silicon, silicon monoxide, a silicon-carbon composite material, a silicon alloy, porous silicon and silicon nanowires.

[0050] In a fourth aspect, a secondary battery is provided, wherein the negative electrode material of the secondary battery comprises the hard carbon negative electrode material or the mixed negative electrode material as described above.

[0051] Further, the counter electrode of the secondary battery includes at least one of metallic lithium and metallic sodium;

[0052] Preferably, the secondary battery includes a lithium secondary battery and a sodium secondary battery;

[0053] Preferably, under the condition that the charge and discharge cut-off voltage is 2.0 to 0 V, the first reversible capacity of the hard carbon negative electrode material for the lithium secondary battery is above 400 mAh / g, and the first efficiency is above 89%;

[0054] Preferably, under the condition that the charge and discharge cut-off voltage is 2.0 to 0 V, the first reversible capacity of the hard carbon negative electrode material for the sodium secondary battery is above 300 mAh / g, and the first efficiency is above 94%.

[0055] Compared with the prior art, the present invention has at least the following beneficial effects:

[0056] The present invention provides a method for preparing a hard carbon negative electrode material. The sodium and / or lithium in the hard carbon precursor react with a passivating substance to form a passivation layer, so that the activity of sodium and / or lithium is reduced, thereby improving the stability and safety of the pre-lithium or pre-sodium precursor in the air, so that the hard carbon material containing lithium and / or sodium can exist stably in the air, and can also improve the processing performance of the pre-lithium or pre-sodium hard carbon negative electrode material when used as a secondary battery negative electrode material, especially can improve the slurry stability of the negative electrode sheet during the preparation process; at the same time, the pre-lithium hard carbon precursor and the pre-sodium hard carbon precursor can compensate for the irreversible lithium ion or sodium ion loss caused by lattice defects in the carbon material and the lithium ions or sodium ions consumed on the SEI because lithium and sodium are introduced in advance, thereby greatly improving the first efficiency of the hard carbon negative electrode material, and is also conducive to its good cycle performance in the battery system.

[0057] The hard carbon negative electrode material provided by the present invention has the characteristics of high specific capacity and high initial efficiency, and also has good processing performance and excellent cycle performance.

[0058] The mixed negative electrode material provided by the present invention has the characteristics of high specific capacity and high initial efficiency, and also has good processing performance and excellent cycle performance.

[0059] The secondary battery provided by the present invention has high power performance and cycle performance, and also has better initial charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0061] Figure 1 This is a SEM image of the hard carbon particles in the hard carbon negative electrode material of Example 1 obtained in Test Example 1 of the present invention;

[0062] Figure 2 A cross-sectional view of hard carbon particles in the hard carbon negative electrode material of Example 1 obtained in Test Example 1 of the present invention;

[0063] Figure 3 The XRD diffraction pattern of the hard carbon negative electrode material of Example 1 obtained in Test Example 1 of the present invention;

[0064] Figure 4 The first charge and discharge curve of the lithium button cell made of the hard carbon negative electrode material of Example 1 obtained in Test Example 2 of the present invention;

[0065] Figure 5 This is the first charge and discharge curve of the sodium button cell made of the hard carbon negative electrode material of Example 4 obtained in Test Example 2 of the present invention. DETAILED DESCRIPTION

[0066] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] As the application fields of new energy secondary batteries continue to expand, the market's requirements for the charging and discharging speed, operating temperature, cycle life, and safety of secondary batteries continue to increase, especially in the fields of consumer electronics and electric vehicles, which have high requirements for the fast charging performance and endurance of secondary batteries. Therefore, it is urgent to develop a hard carbon negative electrode material with high specific capacity and high first coulomb efficiency, so that it has a first efficiency close to that of graphite negative electrode materials.

[0068] In view of this, the present invention provides a hard carbon negative electrode material and a preparation method thereof, which has a specific capacity exceeding that of a graphite negative electrode and an initial efficiency close to that of a graphite negative electrode. When used as a negative electrode material for a secondary battery, it can significantly improve the power performance and cycle performance of the secondary battery and has good initial charge and discharge efficiency.

[0069] According to a first aspect of the present invention, there is provided a method for preparing a hard carbon negative electrode material, comprising the following steps:

[0070] The hard carbon precursor is passivated to obtain a hard carbon negative electrode material;

[0071] Wherein, the hard carbon precursor includes a modified hard carbon precursor;

[0072] The modified hard carbon precursor includes at least one of a pre-lithiation hard carbon precursor and a pre-sodium hard carbon precursor;

[0073] The passivation process comprises the following steps:

[0074] Under the protective atmosphere, the sodium and / or lithium in the hard carbon precursor reacts with the passivation substance to form a passivation layer, thereby reducing the activity of the sodium and / or lithium in the hard carbon precursor.

[0075] The present invention provides a method for preparing a hard carbon negative electrode material. The sodium and / or lithium in the hard carbon precursor react with a passivating substance to form a passivation layer, so that the activity of sodium and / or lithium is reduced, thereby improving the stability and safety of the pre-lithium or pre-sodium precursor in the air, so that the hard carbon material containing lithium and / or sodium can exist stably in the air, and can also improve the processing performance of the pre-lithium or pre-sodium hard carbon negative electrode material when used as a secondary battery negative electrode material, especially can improve the slurry stability of the negative electrode sheet during the preparation process; at the same time, the pre-lithium hard carbon precursor and the pre-sodium hard carbon precursor can compensate for the irreversible lithium ion or sodium ion loss caused by lattice defects in the carbon material and the lithium ions or sodium ions consumed on the SEI because lithium and sodium are introduced in advance, thereby greatly improving the first efficiency of the hard carbon negative electrode material, and is also conducive to its good cycle performance in the battery system.

[0076] In addition, the hard carbon material has a stable structure and very small volume expansion during the charging and discharging process (smaller than graphite negative electrode materials and far lower than silicon-based negative electrodes). It is known as a "zero" strain material in the industry, which enables it to have ultra-long cycle performance and excellent safety performance.

[0077] The present invention does not particularly limit the type of protective atmosphere, and any common protective gas in the art can be used, for example, it can be at least one of nitrogen and argon, but is not limited thereto.

[0078] In a preferred embodiment, the passivating material of the present invention includes but is not limited to at least one of water, alcohol, acid, base and oxide, which is more conducive to reacting with sodium and / or lithium in the hard carbon precursor to form a passivating layer.

[0079] The present invention utilizes at least one of pure water, alcohol, acid solution, alkaline solution and oxide to treat a pre-lithiated or pre-sodiumized hard carbon precursor (pure water, alcohol, acid solution, alkaline solution or oxide is fully contacted with the pre-lithiated or pre-sodiumized hard carbon precursor to cause a reaction to reduce the activity of lithium or sodium) to form a passivation layer, so that it can exist stably in the air, and at the same time can improve the processing performance of the pre-lithiated or pre-sodiumized hard carbon material when used as a negative electrode material for a secondary battery, especially can improve the slurry stability of the negative electrode sheet during the preparation process.

[0080] In a preferred embodiment, the alcohol of the present invention includes but is not limited to at least one of methanol, ethanol, n-propanol, isopropanol, butanol and ethylene glycol, which is more conducive to improving the effect of passivation treatment and forming a passivation layer.

[0081] In a preferred embodiment, the acid of the present invention includes but is not limited to at least one of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, citric acid, formic acid, benzoic acid, acrylic acid, acetic acid, propionic acid, stearic acid, hypochlorous acid and boric acid, which is more conducive to improving the effect of passivation treatment and forming a passivation layer.

[0082] In a preferred embodiment, the base of the present invention includes but is not limited to at least one of lithium carbonate, sodium carbonate, lithium hydroxide and sodium hydroxide, which is more conducive to improving the effect of passivation treatment and forming a passivation layer.

[0083] In a preferred embodiment, the oxide of the present invention includes but is not limited to at least one of manganese heptoxide, sulfur trioxide, phosphorus pentoxide, chromium trioxide, sodium oxide, lithium oxide, calcium oxide, barium oxide, manganese oxide and magnesium oxide, which is more conducive to improving the effect of passivation treatment and forming a passivation layer.

[0084] In a preferred embodiment, the carbon layer spacing d of the hard carbon precursor of the present invention is 002 It is 0.35-0.43nm, for example, it can be 0.35nm, 0.36nm, 0.37nm, 0.38nm, 0.39nm, 0.40nm, 0.41nm, 0.42nm, 0.43nm, but is not limited to this, and may be further preferably 0.36-0.42nm. The hard carbon material of the present invention has a larger carbon layer spacing than graphite (0.34nm), so lithium and sodium ions are easier to embed and remove, and has better power performance.

[0085] In a preferred embodiment, the lithium content in the pre-lithiated hard carbon precursor of the present invention is 0.5-10wt%, for example, it can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, but not limited to this.

[0086] In a preferred embodiment, the sodium content in the pre-sodiumized hard carbon precursor of the present invention is 0.5-10wt%, for example, it can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, but not limited to this.

[0087] In a preferred embodiment, the method for preparing the modified hard carbon precursor of the present invention comprises the following steps:

[0088] The hard carbon raw material is first sintered in an inert atmosphere to obtain a precursor, and then mixed with a lithium source and / or a sodium source for a second sintering to make the precursor contain lithium and / or sodium, thereby obtaining a modified hard carbon precursor.

[0089] The content of lithium or sodium in the hard carbon material is proportional to the amount of lithium source or sodium source added; when the content of lithium or sodium in the hard carbon precursor is too little, the active lithium source or sodium source may be completely consumed during the passivation treatment, resulting in no obvious or no improvement in the first efficiency of the hard carbon negative electrode material; when the content of lithium or sodium in the hard carbon precursor is too much, on the one hand, it will lead to a significant increase in cost, and on the other hand, it will easily lead to spontaneous combustion of the material, because active lithium or sodium is difficult to exist stably in the air, and the increase in its mass proportion will make it difficult to thoroughly passivate the material, and the passivation layer will not be fully formed on the surface of the material, then the exposed active lithium or sodium will react quickly with the air, which may lead to the risk of spontaneous combustion, especially when the air humidity is high, the spontaneous combustion reaction will be more intense.

[0090] In the present invention, the type of the inert atmosphere is not particularly limited, and may be, for example, nitrogen, but is not limited thereto.

[0091] The hard carbon raw material for preparing the hard carbon negative electrode material precursor in the present invention is preferably a substance with higher purity, such as a sugar material or a purified biomass material, that is, it contains less metal impurities and lower ash content after carbonization. The reason is that metal impurities are prone to form local short circuits during the charge and discharge process, which has an adverse effect on the electrochemical performance and safety performance, while excessive ash content will significantly reduce the initial efficiency and cycle performance of the negative electrode material, causing irreversible loss of sodium or lithium ions.

[0092] In the present invention, the hard carbon raw material includes but is not limited to at least one of sugars, polymer resins, biomass materials and carbon products.

[0093] The sugars of the present invention include but are not limited to one or more of fructose, mannose, sucrose, glucose, galactose, galactan, amino sugar, ribose, deoxyribose, starch, cellulose, polysaccharides, pectin, pentose, mannose, mannan, chitin, maltose, gum arabic, glycogen and inulin; polymer resins include but are not limited to one or more of phenolic resins, epoxy resins and polyester resins; biomass materials include but are not limited to one or more of coconut shells, rice shells, peanut shells, pistachio shells and walnut shells; carbon products include but are not limited to one or more of petroleum coke, asphalt coke and coal-based coke.

[0094] The hard carbon raw material of the present invention may be a material that has not been subjected to high-temperature graphitization treatment, which does not mean that it cannot be graphitized. It can be considered as a hard carbon raw material that is difficult to graphitize. When it is sintered at different temperatures, the performance of the obtained carbon negative electrode material is very different; as the sintering temperature increases, the interlayer spacing d of the carbon material increases. 002 Although the gradual decrease can improve the initial efficiency of carbon materials, it will reduce its specific capacity, and the reduction of carbon layer spacing is not conducive to the performance of carbon material characteristics. If the sintering temperature is too low, the initial efficiency of carbon materials will be low, making it difficult to use in batteries. In short, the structures of carbon materials prepared by sintering processes at different temperatures are quite different, and the electrochemical properties they embody are also different.

[0095] In a preferred embodiment, the first sintering temperature is below 1800°C, for example, it can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, but is not limited thereto, and may further preferably be 1000-1600°C.

[0096] In the present invention, the mixing process of the precursor and the lithium source or sodium source can be carried out under the protection of air or nitrogen, depending on the specific material of the lithium source or sodium source. If the lithium source or sodium source is sensitive to humidity, it can be preferably mixed in a dry room, and the air humidity in the dry room is preferably controlled to be below 10%.

[0097] In a preferred embodiment, the mixing mass ratio of the precursor to the lithium source or the sodium source can be 100:(1-20), for example, it can be 100:1, 100:5, 100:10, 100:15, 100:20. The sintering temperature after mixing can be 300-900°C, for example, it can be 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, but not limited to this. The sintering can be carried out under a protective atmosphere of nitrogen or argon. After sintering, the hard carbon precursor contains lithium or sodium element.

[0098] In the present invention, the lithium source includes but is not limited to at least one of lithium powder, lithium tetrafluoroborate, lithium hydride, lithium acetate, lithium stearate, lithium hexafluorophosphate, lithium nitride, lithium fluoride, lithium chloride and lithium bromide.

[0099] In the present invention, the sodium source includes but is not limited to at least one of sodium powder, sodium sulfide, sodium oxide, sodium peroxide, sodium hypochlorite, sodium hydride, sodium nitride, sodium thiosulfate, sodium ethoxide, sodium dichloroacetate, sodium ascorbate and disodium maleate.

[0100] In a preferred embodiment, the preparation method of the present invention further comprises a step of carbon coating the hard carbon precursor to form a carbon coating layer on the surface of the hard carbon precursor after the passivation treatment.

[0101] In the present invention, the surface of part of the precursor after passivation treatment can be carbon-coated. For example, based on the total amount of the hard carbon precursor material after sintering, the proportion of the carbon-coated hard carbon precursor can be 1 to 15wt%, for example, it can be 1wt%, 3wt%, 5wt%, 7wt%, 9wt%, 12wt%, or 15wt%.

[0102] The carbon material after high-temperature treatment has a rich porous structure inside, and is very easy to absorb moisture during subsequent processing or when prepared into finished products and stored, resulting in serious deterioration of its electrochemical properties. Although the moisture adsorbed on the surface of the carbon material can be removed by baking, the moisture adsorbed inside the pores of the carbon material cannot be removed by baking; in order to reduce moisture adsorption, the present invention performs carbon coating on the surface of the precursor to form a carbon coating layer, so that the pores are closed, improving its shortcoming of easy absorption of moisture, and the carbon coating layer can also isolate the infiltration of the electrolyte in the battery system, further improving the structural stability of the hard carbon negative electrode material, so that it has good electrochemical properties.

[0103] In the present invention, the carbon coating step is carried out after the passivation treatment, which means that the carbon coating layer exists in the outermost layer of the hard carbon negative electrode material, which is equivalent to further carbon coating outside the initial passivation layer. On the one hand, it can further improve the stability and safety performance of the pre-lithiation or pre-sodium hard carbon precursor in the air. On the other hand, it can also improve the processing performance of the hard carbon negative electrode material when used as a secondary battery negative electrode material, especially improve the slurry stability of the negative electrode sheet during the preparation process.

[0104] In a preferred embodiment, the average thickness of the carbon coating layer in the present invention can be 10 to 2000 nm, for example, it can be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm, but is not limited to this.

[0105] In the present invention, the carbon coating layer includes but is not limited to a coating layer formed after thermal decomposition of a thermal decomposition raw material, wherein the thermal decomposition raw material includes but is not limited to at least one of asphalt, methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane, hexane, polyvinyl chloride resin, polyamide resin, polyamide, polyethylene glycol, polyethylene, polyvinyl chloride, polystyrene and polypropylene, which is more conducive to the formation of the carbon coating layer.

[0106] According to the second aspect of the present invention, there is provided a hard carbon negative electrode material prepared by any of the preparation methods described above, which has a specific capacity exceeding that of a graphite negative electrode and an initial efficiency close to that of a graphite negative electrode. When used as a negative electrode material for a secondary battery, it can significantly improve the power performance and cycle performance of the secondary battery and has good initial charge and discharge efficiency.

[0107] In a preferred embodiment, the specific surface area of ​​the hard carbon negative electrode material of the present invention can be 1 to 6 m 2 / g, for example, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, but not limited thereto; the median particle size D50 can be 3 to 15 μm, for example, 3 μm, 6 μm, 9 μm, 12 μm, 15 μm, but not limited thereto; the water content can be below 1 wt%; the tap density can be 0.6 to 1.0 g / cm 3 , for example, it can be 0.6 g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , but not limited to this; the compaction density under 5T pressure can be 0.8~1.3g / cm 3 , for example, it can be 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , but not limited to this.

[0108] The specific surface area, median particle size D50, water content, tap density and compacted density of the hard carbon negative electrode material of the present invention are more conducive to improving the comprehensive performance and working performance of the material, so that it can be better applied.

[0109] According to a third aspect of the present invention, there is provided a mixed negative electrode material, comprising any one of the hard carbon negative electrode materials described above and other negative electrode materials.

[0110] In a preferred embodiment, the mass proportion of the hard carbon negative electrode material in the mixed negative electrode material may be greater than 10%.

[0111] In a preferred embodiment, other negative electrode materials include but are not limited to at least one of other carbon-based negative electrode materials and silicon-based negative electrode materials.

[0112] In a preferred embodiment, other carbon-based negative electrode materials include but are not limited to at least one of artificial graphite, natural graphite, mesophase carbon microbeads, carbon nanotubes and graphene.

[0113] In a preferred embodiment, the silicon-based negative electrode material includes but is not limited to at least one of elemental silicon, silicon monoxide, a silicon-carbon composite material, a silicon alloy, porous silicon and silicon nanowires.

[0114] The mixed negative electrode material provided by the present invention has the characteristics of high specific capacity and high initial efficiency, and also has good processing performance and excellent cycle performance.

[0115] According to a fourth aspect of the present invention, there is provided a secondary battery comprising any one of the hard carbon negative electrode materials described above or any one of the mixed negative electrode materials described above.

[0116] The secondary battery provided by the present invention has high power performance and cycle performance, and also has better initial charge and discharge efficiency.

[0117] In a preferred embodiment, the counter electrode of the secondary battery in the present invention includes at least one of metallic lithium and metallic sodium.

[0118] In a preferred embodiment, the secondary battery in the present invention includes a lithium secondary battery and a sodium secondary battery.

[0119] In a preferred embodiment, under the condition that the charge and discharge cut-off voltage is 2.0 to 0 V, the first reversible capacity of the hard carbon negative electrode material for lithium secondary batteries of the present invention is above 400 mAh / g, and the first efficiency is above 89%.

[0120] In a preferred embodiment, under the condition that the charge and discharge cut-off voltage is 2.0 to 0V, the first reversible capacity of the hard carbon negative electrode material for sodium secondary battery of the present invention is above 300 mAh / g, and the first efficiency is above 94%.

[0121] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0122] Example 1

[0123] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0124] The hard carbon raw material is first sintered in a nitrogen atmosphere, then cooled to room temperature, and then broken up and sieved to obtain a precursor, and then mixed with a lithium source in a nitrogen atmosphere for a second sintering (pre-lithiation treatment) to make the precursor contain lithium element to obtain a pre-lithiation hard carbon precursor, which is then passivated and then carbon coated to obtain a hard carbon negative electrode material;

[0125] The hard carbon raw material is starch, and the first sintering temperature is 1300°C;

[0126] The mixing mass ratio of the precursor to the lithium source is 95:5, and the mass content of lithium in the pre-lithiated hard carbon precursor is 5%;

[0127] The lithium source is lithium powder, and the temperature of the second sintering is 600°C;

[0128] The passivation process includes the following steps:

[0129] In a nitrogen atmosphere, the pre-lithiated hard carbon precursor reacts with the introduced ethanol vapor at 200°C for 0.5h, then is cooled to room temperature, and then is broken up and sieved to obtain a passivated material;

[0130] The carbon coating process includes the following steps:

[0131] The passivated material is placed in a CVD rotary furnace, and nitrogen is introduced until the oxygen content in the furnace is less than 100 ppm. The temperature is then raised to 900°C, and acetylene (thermal decomposition raw material) is introduced. The acetylene flow rate is 1.5 L / min, and the ratio of the amount of acetylene introduced (L) / the mass of the passivation material (g) is 0.8. For example, when 100 g of the passivation material is added, the total acetylene flow rate is 80 L. Since the acetylene flow rate is fixed at 1.5 L / min, the continuous introduction time of acetylene is 76.19 min. Acetylene is cracked at high temperature to form a carbon coating layer; then it is cooled to room temperature in a nitrogen atmosphere, and then broken up, sieved and graded to obtain a hard carbon negative electrode material, and its carbon coating layer is observed under a scanning electron microscope, and the thickness is about 70 nm;

[0132] The carbon layer spacing d of the hard carbon negative electrode material prepared in this example 002 The material phase was analyzed by XRD diffractometer (X'Pert3 Powder) and the carbon layer spacing d was calculated. 002 ;

[0133] The particle size D50 of the hard carbon negative electrode material is 8.2 μm, the particle size D100 is 37.1 μm, and the particle size D10 is 3.9 μm. The particle size range is tested using Malvern laser particle size analyzer Mastersizer 3000.

[0134] The specific surface area of ​​the hard carbon negative electrode material is 2.6m 2 / g, the specific surface area of ​​the material was tested using the American Quantachrome NOVA 4000e;

[0135] The water content of the hard carbon negative electrode material is 0.08 wt %, and the water content in the negative electrode material is measured using a Karl Fischer moisture meter.

[0136] Example 2

[0137] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0138] The hard carbon raw material is first sintered in a nitrogen atmosphere, then cooled to room temperature, and then broken up and sieved to obtain a precursor, and then mixed with a lithium source in a nitrogen atmosphere for a second sintering to make the precursor contain lithium element to obtain a pre-lithiated hard carbon precursor, which is then passivated and then carbon coated to obtain a hard carbon negative electrode material;

[0139] The hard carbon raw material is coconut shell, and the first sintering temperature is 1600℃;

[0140] The mixing mass ratio of the precursor to the lithium source is 89:11, and the mass content of lithium in the pre-lithiated hard carbon precursor is 9.76%;

[0141] The lithium source is lithium hydride, and the temperature of the second sintering is 800°C;

[0142] The passivation process includes the following steps:

[0143] In a nitrogen atmosphere, the pre-lithiated hard carbon precursor reacts with the introduced water vapor at 180°C for 1 hour, then is cooled to room temperature, and then is broken up and sieved to obtain a passivated material;

[0144] The carbon coating process includes the following steps:

[0145] The passivated material and asphalt were mixed evenly in a mass ratio of 90:10 and sintered in a nitrogen atmosphere at 1000°C to form a carbon coating layer, and then cooled to room temperature, and then crushed, sieved and graded to obtain a hard carbon negative electrode material, the average thickness of which was 2000nm.

[0146] The carbon layer spacing d of the hard carbon negative electrode material prepared in this example 002 The particle size is 0.37nm, the particle size D50 is 14.1μm, the particle size D100 is 46.2μm, the particle size D10 is 4.7μm, and the specific surface area is 1.7m 2 / g, and the water content is 0.3wt%.

[0147] Example 3

[0148] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0149] The hard carbon raw material is first sintered in a nitrogen atmosphere, then cooled to room temperature, and then broken up and sieved to obtain a precursor, and then mixed with a lithium source in a nitrogen atmosphere for a second sintering to make the precursor contain lithium element to obtain a pre-lithiated hard carbon precursor, which is then passivated and then carbon coated to obtain a hard carbon negative electrode material;

[0150] The hard carbon raw material is phenolic resin, and the first sintering temperature is 1450°C;

[0151] The mixing mass ratio of the precursor to the lithium source is 99:1, and the mass content of lithium in the pre-lithiated hard carbon precursor is 0.6%;

[0152] The lithium source is lithium nitride, and the temperature of the second sintering is 900°C;

[0153] The passivation process includes the following steps:

[0154] In a nitrogen atmosphere, the pre-lithiated hard carbon precursor reacts with the introduced hydrochloric acid vapor at 250°C for 1 hour, then is cooled to room temperature, and then is broken up and sieved to obtain a passivated material;

[0155] The carbon coating process includes the following steps:

[0156] The passivated material and polyvinyl chloride resin were mixed evenly in a mass ratio of 95:5, and then sintered at 900°C in a nitrogen atmosphere to form a carbon coating layer, and then cooled to room temperature, and then crushed, sieved and graded to obtain a hard carbon negative electrode material, and the average thickness of the carbon coating layer was 1200nm;

[0157] The carbon layer spacing d of the hard carbon negative electrode material prepared in this example 002 The particle size is 0.38nm, the particle size D50 is 12.7μm, the particle size D100 is 39.3μm, the particle size D10 is 3.6μm, and the specific surface area is 3.4m 2 / g, and the water content is 0.12wt%.

[0158] Example 4

[0159] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0160] The hard carbon raw material is first sintered in a nitrogen atmosphere, then cooled to room temperature, and then broken up and sieved to obtain a precursor, and then mixed with a sodium source in a nitrogen atmosphere for a second sintering (pre-sodium treatment) to make the precursor contain sodium element, to obtain a pre-sodiumized hard carbon precursor, and then passivated, and then carbon coated to obtain a hard carbon negative electrode material;

[0161] The hard carbon raw material is pitch coke, and the first sintering temperature is 1050°C;

[0162] The mixing mass ratio of the precursor to the sodium source is 95:5, and the mass content of sodium in the pre-sodiumized hard carbon precursor is 5%;

[0163] The sodium source is sodium powder, and the temperature of the second sintering is 500°C;

[0164] The passivation process includes the following steps:

[0165] Under a nitrogen atmosphere, the pre-sodiumized hard carbon precursor reacts with the introduced water vapor at 120°C for 1 hour, then is cooled to room temperature, and then is broken up and sieved to obtain a passivated material;

[0166] The carbon coating process includes the following steps:

[0167] The passivated material and the polyamide resin were mixed uniformly in a mass ratio of 96:4, and then sintered at 950°C in a nitrogen atmosphere to form a carbon coating layer, and then cooled to room temperature, and then crushed, sieved and graded to obtain a hard carbon negative electrode material, and the average thickness of the carbon coating layer was 800nm;

[0168] The carbon layer spacing d of the hard carbon negative electrode material prepared in this example 002The particle size is 0.41nm, the particle size D50 is 8.3μm, the particle size D100 is 37.1μm, the particle size D10 is 2.9μm, and the specific surface area is 4.1m 2 / g, and the water content is below 0.36wt%.

[0169] Example 5

[0170] A method for preparing a hard carbon negative electrode material comprises the following steps:

[0171] The hard carbon raw material is first sintered in a nitrogen atmosphere, then cooled to room temperature, and then broken up and sieved to obtain a precursor, and then mixed with a sodium source in a nitrogen atmosphere for a second sintering to make the precursor contain sodium element to obtain a pre-sodiumized hard carbon precursor, which is then passivated and then carbon-coated to obtain a hard carbon negative electrode material;

[0172] The hard carbon raw material is cellulose, and the first sintering temperature is 1200°C;

[0173] The mixing mass ratio of the precursor to the sodium source is 96:4, and the mass content of sodium in the pre-sodiumized hard carbon precursor is 3.9%;

[0174] The sodium source is sodium hydride, and the temperature of the second sintering is 900°C;

[0175] The passivation process includes the following steps:

[0176] Under a nitrogen atmosphere, the pre-sodiumized hard carbon precursor reacts with the introduced sodium hydroxide solution vapor at a temperature of 200°C for 1 hour, and then is cooled to room temperature, and then is broken up and sieved to obtain a passivated material;

[0177] The carbon coating process includes the following steps:

[0178] The passivated material and polystyrene were mixed evenly in a mass ratio of 90:10 and sintered in a nitrogen atmosphere at a temperature of 1100°C to form a carbon coating layer, and then cooled to room temperature, and then crushed, sieved and graded to obtain a hard carbon negative electrode material, and the average thickness of the carbon coating layer was 300nm;

[0179] The carbon layer spacing d of the hard carbon negative electrode material prepared in this example 002 The particle size is 0.40nm, the particle size D50 is 4.1μm, the particle size D100 is 29.5μm, the particle size D10 is 1.2μm, and the specific surface area is 5.7m 2 / g, and the water content is 0.6wt%.

[0180] Example 6

[0181] The difference between this embodiment and embodiment 1 is that the hard carbon raw material of this embodiment is epoxy resin, and the remaining steps and parameters thereof refer to embodiment 1 to obtain a hard carbon negative electrode material.

[0182] Example 7

[0183] The difference between this embodiment and embodiment 1 is that the lithium source of this embodiment is lithium hexafluorophosphate, and the remaining steps and parameters are referred to embodiment 1 to obtain a hard carbon negative electrode material.

[0184] Example 8

[0185] The difference between this embodiment and embodiment 1 is that the thermal decomposition raw material of this embodiment is methane, and the remaining steps and parameters thereof refer to embodiment 1 to obtain a hard carbon negative electrode material.

[0186] Example 9

[0187] The difference between this embodiment and embodiment 1 is that no carbon coating treatment is performed in the preparation method of this embodiment, and the rest is the same as that of embodiment 1 to obtain a hard carbon negative electrode material.

[0188] Comparative Example 1

[0189] The difference between this comparative example and Example 1 is that the precursor in this comparative example is not subjected to pre-lithium treatment, and the rest is the same as Example 1 to obtain a hard carbon negative electrode material.

[0190] Comparative Example 2

[0191] The difference between this comparative example and Example 4 is that the precursor in this comparative example is not subjected to pre-sodium treatment, and the rest is the same as Example 4 to obtain a hard carbon negative electrode material.

[0192] Comparative Example 3

[0193] The difference between this comparative example and Example 1 is that no passivation treatment is performed in the preparation method of this comparative example, and the rest is the same as Example 1 to obtain a hard carbon negative electrode material.

[0194] Comparative Example 4

[0195] The difference between this comparative example and Example 4 is that no passivation treatment is performed in the preparation method of this comparative example, and the rest is the same as Example 4 to obtain a hard carbon negative electrode material.

[0196] The process parameters and physical property indicators of the preparation methods in Examples 1-9 and Comparative Examples 1-4 are shown in Table 1.

[0197] Table 1

[0198]

[0199] Test Example 1

[0200] The morphology of the hard carbon negative electrode material obtained in Example 1 was analyzed using a JSM-7160 scanning electron microscope from Japan Electronics Co., Ltd. Figure 1 ,As can be seen from the figure, the hard carbon particles are evenly distributed and there is no obvious fine powder.

[0201] The cross-sectional plane sample of the hard carbon negative electrode material of Example 1 was prepared by using a SEM Mill ion beam cutting and polishing system (Gatan 685Fischione 1061) for SEM imaging observation and microscopic analysis. Figure 2 As can be seen from the figure, there is a uniform and complete carbon coating layer on the surface of the hard carbon particles. By measuring with a ruler, the thickness of the carbon coating layer is about 70nm.

[0202] The phase analysis of the hard carbon negative electrode material of Example 1 was performed using an XRD diffractometer (X'Pert3 Powder). Figure 3 , the carbon layer spacing d is calculated 002 , we know that the carbon layer spacing d of the hard carbon negative electrode material is 002 It is 0.39nm.

[0203] Test Example 2

[0204] The hard carbon negative electrode material obtained in Example 1 was made into a lithium button battery, and the first charge and discharge curve of the lithium button battery was obtained by the lithium button battery test method. Figure 4 It can be seen that under the condition of charge and discharge cut-off voltage of 2.0~0V, the first reversible capacity of the hard carbon negative electrode material is above 409mAh / g, and the first efficiency is 91.4%.

[0205] The hard carbon negative electrode material obtained in Example 4 was made into a sodium button battery, and the first charge and discharge curve of the sodium button battery was obtained by the sodium button battery test method. Figure 5 It can be seen that under the condition of charge and discharge cut-off voltage of 2.0~0V, the first reversible capacity of the hard carbon negative electrode material is above 320mAh / g, and the first efficiency is 94.5%.

[0206] Test Example 3

[0207] The hard carbon negative electrode materials obtained in Examples 1-3, Examples 6-9, Comparative Example 1 and Comparative Example 3 were respectively made into lithium button batteries, which were then tested. The results are shown in Table 2.

[0208] The lithium button cell is composed of a commercial negative electrode shell, a positive electrode shell, a separator, a lithium sheet, nickel foam, a pole piece and an electrolyte;

[0209] The conductive agent is acetylene black, the binder is CMC SBR PVDF LA133 BP-7, and the solvent is ultrapure water;

[0210] The electrolyte is composed of three parts: lithium salt, solvent and additive. The lithium salt is lithium hexafluorophosphate, the solvent is ethylene carbonate (EC), and the additive is dimethyl carbonate (DMC).

[0211] The thickness of the diaphragm is 30um, and the current collector is copper foil (thickness is 12um).

[0212] The preparation method of a lithium button cell comprises the following steps:

[0213] The hard carbon negative electrode material, conductive carbon black and binder are mixed in pure water at a mass ratio of 96:1:3, homogenized, and the solid content is controlled to be 48%, coated on a copper foil current collector, and then vacuum baked at a temperature of 100-110° C. for 4-8 hours, pressed into shape, and punched to obtain a negative electrode sheet;

[0214] The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1).

[0215] The obtained button half-cell was subjected to charge and discharge tests (the button cell testing equipment was the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.), the test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV 50uA, 0.01C DC to 0V, 0V CV 20uA, Rest10min, 0.2C CC to 2V, and the first reversible capacity and efficiency of the hard carbon negative electrode material were obtained.

[0216] The hard carbon negative electrode materials obtained in Examples 4-5, Comparative Examples 2 and Comparative Example 4 were respectively made into sodium button cells (the counter electrode was a metallic sodium sheet). The preparation method was referenced to the above-mentioned lithium button cells, and then tested. The test process was 0.2C DC to 0V, 0.05C DC to 0V, 0V CV 50uA, 0.01C DC to 0V, 0V CV 20uA, Rest 10min, 0.2C CC to 2V. The results are shown in Table 3.

[0217] Table 2

[0218]

[0219] Table 3

[0220]

[0221]

[0222] It can be seen from the above table that the initial efficiency and cycle performance of the hard carbon negative electrode material are significantly improved after pre-lithiation; the performance of the hard carbon negative electrode materials obtained from different hard carbon raw materials, lithium sources and their ratios, and different preparation processes will be different.

[0223] In Comparative Examples 1-2, the precursor was not pre-lithium or pre-sodium treated, and the initial efficiency and cycle performance of the resulting hard carbon negative electrode material were significantly worse. This is because there are a large number of lattice defects in the internal structure of the hard carbon negative electrode material. Although these lattice defects can improve the reversibility of the hard carbon negative electrode, these lattice defects also lead to the low initial coulombic efficiency of the hard carbon negative electrode material and too fast cycle decay in the early stage.

[0224] In Comparative Examples 3-4, the hard carbon precursor was not passivated after pre-lithium or pre-sodium treatment, and the initial efficiency and cycle performance of the resulting hard carbon negative electrode material were significantly deteriorated. This is because active lithium or sodium is difficult to exist stably in the air. If passivation treatment is not performed, the exposed active lithium or sodium will quickly react with the air, causing the electrochemical properties of the hard carbon material to deteriorate sharply.

[0225] The hard carbon negative electrode material prepared by the preparation method of the present invention is tested by XRD diffractometer, and the carbon layer spacing d is calculated. 002 At 0.35-0.43nm, the hard carbon negative electrode material contains lithium or sodium. When it is used as the negative electrode material of a secondary battery (the electrode is metallic lithium or metallic sodium), under the condition of a charge and discharge cut-off voltage of 2.0-0V, the first reversible capacity of the hard carbon negative electrode material for a lithium secondary battery is above 400mAh / g, and the first efficiency is above 89%. The first reversible capacity of the hard carbon negative electrode material for a sodium secondary battery is above 300mAh / g, and the first efficiency is above 94%.

[0226] The hard carbon negative electrode material provided by the present invention has significantly higher initial efficiency than traditional hard carbon negative electrode materials. When used as a negative electrode material of a secondary battery, it can significantly improve the power performance and cycle performance of the secondary battery.

[0227] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, characterized in that: The following steps are involved: The hard carbon precursor is passivated to obtain the hard carbon negative electrode material; The hard carbon precursor includes a modified hard carbon precursor; The modified hard carbon precursor includes at least one of a pre-lithiation hard carbon precursor and a pre-sodium hard carbon precursor; The passivation process comprises the following steps: Under the protective atmosphere, the sodium and / or lithium in the hard carbon precursor reacts with the vapor of the passivating substance to form a passivation layer, so that the activity of the sodium and / or lithium in the hard carbon precursor is reduced, and a passivated material is obtained; The protective atmosphere comprises at least one of nitrogen and argon; The passivating substances are water, hydrochloric acid and sodium hydroxide solution.

2. The preparation method according to claim 1, characterized in that: The carbon layer spacing d of the hard carbon precursor 002 It is 0.35~0.43nm.

3. The preparation method according to claim 1, characterized in that: The carbon layer spacing d of the hard carbon precursor 002 It is 0.36~0.42nm.

4. The preparation method according to claim 1, characterized in that: The lithium content in the pre-lithiated hard carbon precursor is 0.5-10wt%.

5. The preparation method according to claim 1, characterized in that: The sodium content in the pre-sodiumized hard carbon precursor is 0.5-10wt%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The method for preparing the modified hard carbon precursor comprises the following steps: The hard carbon raw material is first sintered in an inert atmosphere to obtain a precursor, and then mixed with a lithium source or a sodium source for a second sintering so that the precursor contains lithium or sodium, thereby obtaining a modified hard carbon precursor; The inert atmosphere includes nitrogen.

7. The preparation method according to claim 6, characterized in that: The temperature of the first sintering is below 1800°C.

8. The preparation method according to claim 6, characterized in that: The first sintering temperature is 1000-1600°C.

9. The preparation method according to claim 6, characterized in that: The lithium source includes at least one of lithium powder, lithium tetrafluoroborate, lithium hydride, lithium acetate, lithium stearate, lithium hexafluorophosphate, lithium nitride, lithium fluoride, lithium chloride and lithium bromide.

10. The preparation method according to claim 6, characterized in that: The sodium source includes at least one of sodium powder, sodium sulfide, sodium oxide, sodium peroxide, sodium hypochlorite, sodium hydride, sodium nitride, sodium thiosulfate, sodium ethoxide, sodium dichloroacetate, sodium ascorbate and disodium maleate.

11. The preparation method according to claim 6, characterized in that: The second sintering temperature is 300-900°C.

12. The preparation method according to claim 1, characterized in that: After the passivation treatment, the step of carbon coating the hard carbon precursor to form a carbon coating layer on the surface of the hard carbon precursor is also included; The average thickness of the carbon coating layer is 10-2000 nm.

13. The preparation method according to claim 12, characterized in that: The carbon coating layer includes a coating layer formed after the thermal decomposition raw material is thermally decomposed; The thermal decomposition raw material includes at least one of asphalt, methane, ethane, ethylene, acetylene, propane, propylene, acetone, butane, butene, pentane, hexane, polyvinyl chloride resin, polyamide resin, polyamide, polyethylene glycol, polyethylene, polyvinyl chloride, polystyrene and polypropylene.

14. A hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 13, characterized in that: The specific surface area of ​​the hard carbon negative electrode material is 2.6 m 2 / g, 1.7m 2 / g, 3.4m 2 / g, 4.1m 2 / g, 5.7m 2 / g, 3.1m 2 / g or 4.2m 2 / g; The median particle size D50 of the hard carbon negative electrode material is 8.2 μm, 14.1 μm, 12.7 μm, 8.3 μm, 4.1 μm, 7.9 μm or 10.5 μm; The water content of the hard carbon negative electrode material is below 1wt%; The compaction density of the hard carbon negative electrode material at a pressure of 5T is 0.8-1.3 g / cm 3 .

15. A secondary battery, characterized in that: The negative electrode material of the secondary battery comprises the hard carbon negative electrode material according to claim 14.

Citation Information

Patent Citations

  • Hard carbon composite material, preparation method thereof and lithium ion battery

    CN114436240A